Scrapbook Media on Indonesian Language Learning Outcomes for Single Sentence Material for Grade III Students of SD Negeri 5 Tubanan - Puspitasari, Della; Wiranti, Dwiana Asih (Jurnal Evaluasi dan Pembelajaran, 2025)
The discovery of errors in writing single sentences taught to third grade students at SD Negeri 5 Tubanan became the inspiration for the title of this research. The aim of this research is to evaluate the efficacy of scrapbook learning media on the acquisition of Indonesian through learning single sentence content. 22 third grade students from SD Negeri 5 Tubanan participated in this research. The research approach uses quantitative experiments and data collection procedures through the use of 25 multiple choice questions for pre and post tests. The t-test was used as part of the data analysis procedure. The average posttest score was 71.09, while the average pretest score was 51.64, as shown by the paired sample statistical test. The paired sample correlation test produces a significance level of 0.023, which is less than the predetermined limit of 0.05. In addition, a significance value of less than 0.001 is indicated by the results of the Paired Sample T Test which is smaller than the significance limit of 0.05. Based on these results, it can be concluded that learning activities with single sentence learning material using scrapbook media are effective.